A DESIGUALDADE DA RENDA RURAL NO NORDESTE: UMA ANÁLISE DA DESAGREGAÇÃO DO COEFICIENTE DE GÍNI E DA SENSIBILIDADE DO ÍNDICE DE BEM-ESTAR DE SEN - Mariano, Jorge Luiz (2009)
The objective of this work is to identify the sources of income inequality in rural Northeast Brazil using Gini coefficient decomposition methods. This study seeks to analyze the effects of small and large farmers in inequality when there is an increase in a rural income source. In addition, it analyzes the variability and sensibility of the Sen Welfare function to a change in a rural income source of the small farms. Results show that agriculture was the income source that most contributed to inequality in the 1980's, while livestock contributed to income distribution. The results by farm size show that non-farm economy contributed to income distribution among small farmers, and to income concentration among large size producers.